Influence of Information Technology Management on the Organizational Performance of the Small and Medium-Sized Enterprises - JOSE MELCHOR MEDINA QUINTERO (2017)
This research analyzes the degree of influence that the use of information management and information technology has on the organizational performance in terms of competitiveness, innovation, and productivity of the small and medium-sized enterprises in the central region of the state of Tamaulipas, Mexico. Data were collected by means of a questionnaire and analyzed by using a Partial Least Squares; the results show a greater support from the information technology and information management variables to innovation (standardized path=0.418 and 0.367, and p<0.05* both). This means that by having an efficient information management process, enterprises are able to get new goods/services, to identify new markets and to face competition.